The Influence of Corporate Boundary Personnel Guanxi and Organizational Loyalty on Opportunistic Intentions – Based on Theory of Reasoned Action Model - Zhao, Shu-kuan; Cai, Jia-ming (Frontiers in Psychology, 2022)
To understand the mechanism of boundary personnel opportunistic behaviors in collaborative R&D projects to reduce the risk of companies suffering from opportunism in collaboration. This study is conducted based on the context of collaborative R&D in the equipment manufacturing industry in Northeast China. This research mainly explored the mechanism of boundary personnel opportunism intentions. Drawing on the theory of reasoned action (TRA), this study investigated the relationship between boundary personnel Guanxi, organizational loyalty, opportunism attitudes, subjective norms, and intentions. In addition, this research examined the moderating role of the degree of dependence on the collaborator. 524 valid questionnaires were finally collected. The data analysis results suggested that Guanxi inhibits opportunism attitudes and subjective norms. Organizational loyalty promotes opportunism attitudes and subjective norms. Opportunism attitudes and subjective norms positively predict intentions. Opportunism attitudes mediate between organizational loyalty and opportunism intentions. Opportunism subjective norms mediate between Guanxi and opportunism intentions. Opportunism subjective norms also mediate between organizational loyalty and opportunism intentions Dependence on the collaborator positively moderates the relationship between opportunism attitudes and intentions. Therefore, it can be argued that in collaborative R&D in the equipment manufacturing industry, the corporate could stimulate boundary personnel to build good Guanxi to eliminate opportunism. At the same time, companies should lead employees to show loyalty properly, which opportunism is not wise in collaborative R&D. Finally, enterprises should objectively understand and evaluate the dependence relationship between the two partners in collaborative R&D to adopt the right strategy.